Pengaruh City Branding"Bima Maja Labo Dahu"(Malu Dan Takut) Terhadap City Image Dan Keputusan Berkunjung Wisatawan Ke Kabupaten Bima" (Studi Terhadap Yang Berkunjung Di Pantai Lariti) - Ayatullah khomaini; N. Rachma; M. Hufron (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
AbstractThis study aims to determine and analyze the effect of city branding "bima maja labo dahu" (shame and fear) on the image of the city the decision to visit tourists to the district of bima in tourists on the coast of lariti. This research was conducted using data collection with the help of questionnaires distributed through random sampling techniques with a sample of 91 people who are tourists visiting the coast of the district of Lariti Bima. Data analysis in this study uses SPSS (statistical products and service solutions) with data testing techniques used are validity, reliability, data normality, path analysis, hypothesis testing, partial test (t) and multiple tests. The showed that city branding has direct effect for city image, city branding has direct effect for visiting decisions, city image has in a direct effect for visiting decisions. City imagery does not directly influence decisions about visits through the city image as an intervention variable.Keywords: City Branding, City Image, and Decision to Visit